Associations of modified triglyceride-glucose indices and the triglyceride/high-density lipoprotein ratio with all-cause and cause-specific mortality in the general population: an analysis of the UK biobank database - Zihao Zhang; Haihua Guo; Zhen Sun; Dandan Zhang; Yujing Lin; Liangyu Huang; Zexin Guo; Lan Tan (Lipids in Health and Disease)
Abstract Background This study investigates the associations between modified triglyceride-glucose (TyG) indices and the triglyceride-to-high-density lipoprotein (TG/HDL) ratio, which are recognized as simple surrogate indicators of insulin resistance, with all-cause and cause-specific mortality. Methods A cohort of 410,515 participants from the UK Biobank was analyzed. Cox proportional hazard models and restricted cubic spline regression analyses were employed to examine the relationships between the TyG index, TyG-body mass index (TyG-BMI), TyG-waist circumference (TyG-WC), TG/HDL ratio, and all-cause and cause-specific mortality. Structural equation modeling was employed to elucidate the associations between the TyG index, TG/HDL ratio, inflammation, metabolism, and mortality. Results The TyG index, TyG-WC, and TG/HDL ratio were associated with an increased risk of all-cause mortality by 3.7% (HR 1.037 [1.016, 1.059]), 0.1% (HR 1.001 [1.024, 1.031]), and 1.5% (HR 1.015 [1.006, 1.025]), respectively. Restricted cubic spline regression models revealed nonlinear trends in the TyG index, TyG-BMI, TyG-WC, and TG/HDL ratio in relation to both all-cause and cause-specific mortality (P for nonlinearity < 0.05). TyG index and TG/HDL ratio exhibited a J-shaped relationship with all-cause mortality as well as mortality from cancer, cardiovascular diseases, and respiratory diseases. Similarly, TyG-BMI demonstrated an L-shaped association with all-cause mortality and mortality due to cancer, cardiovascular diseases, and respiratory diseases. Additionally, TyG-WC was associated with a progressively increasing mortality risk once it exceeded a certain threshold. Structural equation modeling demonstrated that the TyG index and TG/HDL ratio influenced mortality through inflammation and lifestyle factors. Conclusions In conclusion, TyG, TyG-BMI, TyG-WC, and TG/HDL ratio are significantly associated with all-cause and cause-specific mortality in the general population.These associations appear to be linked to inflammation and lifestyle.